The Effect of PhET Simulation-Assisted Guided Inquiry Learning Model on Students' Critical Thinking Ability in Elasticity Material - Ivan Ardisa; Ni Nyoman Sri Putu Verawati; Gunawan Gunawan; Syahrial Ayub (Department of Physics Education, Universitas Mataram, 2022)
This study aims to determine the effect of PhET simulation-assisted guided inquiry learning model on students' critical thinking skills in Elasticity material. The type of research used is quasi-experimental with Nonequivalent Control Group Design. The population in this study were all students of class XI IPA at SMAN 1 Pringgabaya. The sample of this study was class XI H and class XI I, totaling 63 students, while the sampling technique was cluster random sampling method. The sample used in this study was class XI I (experimental class, totaling 32 people) and class XI H (control class, totaling 31 people). Before given the treatment, both classes were given an initial test to determine their initial ability. Based on the results of the initial test homogeneity test, the two samples had the same initial ability. The final test results for students' critical thinking skills obtained an average score of 79.45 with the highest score of 95 for the experimental class and an average of 74.27 with the highest score of 90 for the control class. The research hypothesis was tested with parametric statistical tests in the form of independent t-test variance. Such decision was taken on the basis of the testing. That is, the Sig (2-tailed) value of 0.028 is smaller than the significance level (α) of 0.05, and hence (H0) is rejected and (H1) is accepted. Thus, it can be interpreted that PhET simulation-assisted guided inquiry learning model has an effect on students' critical thinking abilities.